A Caged, Destabilized, Free Radical Intermediate in the Q‐Cycle. Issue 14 (5th September 2013) - Vennam, Preethi R.; Fisher, Nicholas; Krzyaniak, Matthew D.; Kramer, David M.; Bowman, Michael K.
Abstract The Rieske/cytochrome b complexes, also known as cytochrome bc complexes, catalyze a unique oxidant‐induced reduction reaction at their quinol oxidase (Qo) sites, in which substrate hydroquinone reduces two distinct electron transfer chains, one through a series of high‐potential electron carriers, the second through low‐potential cytochrome b. This reaction is a critical step in energy storage by the Q‐cycle. The semiquinone intermediate in this reaction can reduce O2 to produce deleterious superoxide. It is yet unknown how the enzyme controls this reaction, though numerous models have been proposed. In previous work, we trapped a Q‐cycle semiquinone anion intermediate, termed SQo, in bacterial cytochrome bc1 by rapid freeze‐quenching. In this work, we apply pulsed‐EPR techniques to determine the location and properties of SQo in the mitochondrial complex. In contrast to semiquinone intermediates in other enzymes, SQo is not thermodynamically stabilized, and can even be destabilized with respect to solution. It is trapped in Qo at a site that is distinct from previously described inhibitor‐binding sites, yet sufficiently close to cytochrome bL to allow rapid electron transfer. The binding site and EPR analyses show that SQo is not stabilized by hydrogen bonds to proteins. The formation of SQo involves "stripping" of both substrate ‐OH protons during the initial oxidation step, as well as conformational changes of the semiquinone and Qo proteins. The resulting charged radical is kinetically trapped, rather than thermodynamically stabilized (as in most enzymatic semiquinone species), conserving redox energy to drive electron transfer to cytochrome bL while minimizing certain Q‐cycle bypass reactions, including oxidation of prereduced cytochrome b and reduction of O2.